PENGARUH PELAKSANAAN SURGICAL SAFETY CHECKLIST TERHADAP SASARAN KESELAMATAN PASIEN BEDAH - Bambang Priyo Sudarko (LPPMK STIKES Widyagama Husada, 2022)
ABSTRACT The implementation of surgical safety is a medical procedure that aims to save lives, prevent disabilities and complications. A literature search was carried out in December 2020 using Scient Direct, PubMed, and Google Scholar. Keywords are adjusted to the Medical Subject Heading (MeSH), namely ,, “Surgical Safety Checklist” OR “Patient Safety Goals”, OR “Perioperative Nurse. The search results were 156 similar articles so they were excluded and the remaining 11 articles. The researcher then conducted a screening based on the title (n = 156), abstract (n = 23) and full text (n = 10) which was adjusted to the theme of the literature review. The assessment that was as 10 articles that can be used in the literature review, there is a significant effect of implementing the surgical safety checklist and have an effect on patient safety goals. The goal of patient safety is very important for the surgical process because it reduces the adverse effects that occur related to the patient's life. The failure factors of surgery problems can be in many aspects, the perception of fatigue of the staff, and the lack of alertness of the staff. Key words: Surgical, Safety, Checklist, Perioperative ABSTRAK Pelaksanaan surgical safety bertujuan menyelamatkan nyawa, mencegah kecacatan dan komplikasi. Metode penelitian Literature review merupakan rangkuman menyeluruh studi penelitian. Pencarian pada Desember 2020 menggunakan tiga database, yaitu Scient Direct, PubMed, dan Google Scholar. Kata kunci dengan Medical Subject Heading (MeSH) yaitu,, “Surgical Safety Checklist” OR “Sasaran Keselamatan Pasien”, OR “Perawat Perioperatif”. Hasil pencarian terdapat 156 artikel yang sama sehingga tersisa 10 artikel. Peneliti skrining berdasarkan judul (n = 156), abstrak (n = 23) dan full text (n = 10) yang disesuaikan dengan tema literature review. Assessment kelayakan didapatkan sebanyak 10 artikel yang di review ada pengaruh yang signifikan. Sasaran keselamatan mengurangi efek buruk yang terjadi berkaitan dengan nyawa pasien .Faktor kegagalan masalah operasi bisa dari segi banyak aspek, kelelahan persepsi petugas, serta kurangnya kewaspadaan petugas . Kata Kunci: Surgical, Safety, Checklist, Perioperative